Pragmatic Performance in Focus: The Case of Saudi Graduates Giving Advice in English - Aljasir, Nouf (Journal of Humanities & Social Sciences, 2020)
This mixed-method study was conducted to investigate the pragmatic performance of different groups of Saudi individuals when speaking English. More specifically, the study compared the types of strategies employed by graduates in the humanities, science, and English when giving advice in English. The study also examined the extent to which the participants varied their choices of advice-giving linguistic realizations according to their interlocutor’s social status. The possible influence of gender on strategy use was also explored. A total of 212 participants took part in this research, and the data were triangulated from a variety of sources: a discourse completion task (DCT), role plays, and retrospective interviews. The data analysis revealed that the participants’ linguistic competence seemed to have a significant influence on their pragmatic performance in terms of the variety of advice-giving structures available to them and their abilities to adapt their use according to the social situation. There was, however, evidence of pragmatic transfer across all groups’ responses, which could be attributed to their lack of awareness of the target community’s speech conventions. The study concluded with a discussion of the pedagogical implications of the findings and suggestions for future research.